Strategi Komunikasi Hanka Parfume Di Masa Pandemi Covid-19 - Ramadhani Siregar, Faridah; Achiriah, Achiriah; Abidin, Syahrul (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research is entitled “Hanka Parfume Communication Strategy During the Covid-19 Pandemic. The purpose of this study is to find out how the communication strategy used by Hanka Perfume to survive the Covid-19 era and its obstacles. The theory used to explore this research is the 4P theory. The method used in this study is a qualitative descriptive method with the research informants used in this research being the owners of Hanka parfume and several consumers of Hanka parfume. The results of the study show that the marketing communication strategy through advertising has gone well because the company advertises through Instagram media and the promos are given so that it can be known by the public. Furthermore, personal selling activities carried out by the company are by placing marketing employees who directly offer promo packages to buyers.